Analisis Kepuasan Pengguna SIPD-RI dengan Menggunakan Kriteria Delone And Mclean Success System Model: Studi Kasus di DPMPTSP Kota Bandung - Nafira Iftitah Maulida Yanuar; Siti Kustinah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze user satisfaction with the Indonesian Regional Government Information System (SIPD-RI) at the Investment and One-Stop Integrated Service Office (DPMPTSP) of Bandung City using the DeLone and McLean Success System Model criteria. The research focuses on two main indicators: system quality and information quality. A descriptive qualitative method was employed, with data collected through interviews, observations, and document analysis. The findings reveal that the SIPD-RI system quality still faces challenges, such as technical issues (errors, timeouts), suboptimal integration, and limitations in certain modules. Meanwhile, the information quality is considered relevant and accurate, although some data remain incomplete and face delays in presentation. These results are expected to provide input for local governments and system developers to improve the effectiveness, efficiency, and user satisfaction in utilizing SIPD-RI.